Artificial Intelligence Inspired by Biological System: Techniques and Applications - Prabuwono, Anton Satria (Prosiding SNPBS (Seminar Nasional Pendidikan Biologi dan Saintek), 2021)
Artificial Intelligence Inspired by Biological System: Techniques and Applications